Distribution and Frequency of ABO and Rhesus (D) Blood Groups in Somalia: A Retrospective Study on Students of Jazeera University, Mogadishu-Somalia. (30th January 2022) - Mohamud, Mohamed Hayir Tahlil; Aweis, Abdullah Dahir H.; Adam, Abdiwahab Sheikh Elmi; Mohamed, Farhia Abdullahi; Fidow, Safia Qasim; Mohamed, Lul Mohamud
Abstract : Background . There are differences in the distribution and frequency of ABO and D blood groups in different populations of the world. Relatively very little information is available about blood group distributions in the Somali population. Objectives: To identify the distribution and frequency of ABO and D blood groups among the Somali people. Methods . A retrospective cross-sectional study of 1811 enrolled students of Jazeera University was conducted in Jazeera University diagnosis and research center, Mogadishu-Somalia from December 2017 to December 2020. The result was presented as the frequency of each blood group with percentage. A Fisher's exact test was carried out to test the significant association of the ABO blood group with sex and D antigen with sex. Results . Blood group O was the most prevalent (61%), followed by A (27%), B (10%), and AB (2%). The D-antigen was present in 97% of participants and 3% were D-negative. The distribution of O+, A+, B+, AB+ among D-positive subjects were 62%, 27%, 9% and 2.0% while that of O-, A-, B- and AB- among D-negative subjects were 57%, 27%, 12% and 3%, respectively. The frequencies of ABO and D-antigens in both male and female subjects were O > A > B > AB. However, this study found no significant difference of ABO with Sex and D-antigens with sex ( P-value >0.05). Conclusions . The frequency of ABO and D blood groups among the Somalia population was found to be O > A > B > AB which was similar to those reported from most East African populations.